Enhancing the long-cycling performance of a LiNi0.8Co0.15Al0.05O2@LaNiO3 cathode material by surface modification. Issue 5 (16th February 2022) - Fan, Ju; Hu, Guorong; Su, Haodong; Shi, You; Du, Ke; Peng, Zhongdong; Sun, Qian; Zhang, Yinjia; Wu, Kaipeng; Cao, Yanbing
Abstract : Herein, the introduction of hexagonal LaNiO3 on the surface of LiNi0.8 Co0.15 Al0.05 O2 provides a protective and adaptable ultrathin layer to stabilize the microstructure of Ni-rich layered cathode materials, enhancing the electrochemical and thermal stability. Abstract : High-energy density and low-cost Ni-rich layered oxide cathode materials for lithium-ion batteries for electric vehicles have been one of the most popular and meaningful research challenges in recent years. However, chemical instability and capacity fade are the most intractable problems to overcome in the practical applications of Ni-rich layered oxides. Herein, the introduction of hexagonal LaNiO3 (LN) on the surface of LiNi0.8 Co0.15 Al0.05 O2 (NCA) provides a protective and adaptable ultrathin layer to stabilize the microstructure of Ni-rich layered cathode materials. The LN forms a robust "lattice matching" compatible interface structure at the LN/NCA interface through atomic diffusion Ni–O–M bonding, which not only improves the bonding strength and reduces the interface stress of the modified layer, but also decreases the resistance of Li + charge transport through the interface layer. The LN coating inhibits the surface structure phase transition and the accumulation of inactive impurities and reduces the electrochemical polarization. Via the modification of multi-functional inorganic LaNiO3, the electrochemical and thermal stabilities of NCA have been significantly enhanced. This work shows that the formation of atomic-level interface bonds between the modified layer and the matrix material is a good choice for enhancing the stability of Ni-rich layered oxide electrodes for high-energy lithium-ion batteries.